Feasibility and tolerability of ophthalmic virtual reality as a medical communication tool in children and young people. Issue 2 (14th May 2021) - Maloca, Peter M.; Williams, Emily A.; Mushtaq, Faisal; Rueppel, Andreas; Müller, Philipp L.; Lange, Clemens; de Carvalho, Emanuel R.; Inglin, Nadja; Reich, Michael; Egan, Catherine; Hasler, Pascal W.; Tufail, Adnan; et al.
Abstract: Purpose: Virtual reality (VR) can be useful in explaining diseases and complications that affect children in order to improve medical communications with this vulnerable patient group. So far, children and young people's responses to high‐end medical VR environments have never been assessed. Methods: An unprecedented number of 320 children and young people were given the opportunity to interact with a VR application displaying original ophthalmic volume data via a commercially available tethered head‐mounted display (HMD). Participants completed three surveys: demographics and experience with VR, usability and perceived utility of this technology and the Simulator Sickness Questionnaire. The second survey also probed participants for suggestions on improvements and whether this system could be useful for increasing engagement in science. Results: A total of 206 sets of surveys were received. 165 children and young people (84 female) aged 12–18 years (mean, 15 years) completed surveys that could be used for analysis. 69 participants (47.59%) were VR‐naïve, and 76 (52.41%) reported that they had previous VR experience. Results show that VR facilitated understanding of ophthalmological complications and was reasonably tolerated. Lastly, exposure to VR raised children and young people's awareness and interest in science. Conclusions: The VR platform used was successfully utilized and was well accepted in children to display and interact with volume‐rendered 3D ophthalmological data. Virtual reality (VR) is suitable as a novel image display platform in ophthalmology to engage children and young people.